2019
DOI: 10.1093/mnras/stz3397
|View full text |Cite
|
Sign up to set email alerts
|

Rapid luminosity decline and subsequent reformation of the innermost dust distribution in the changing-look AGN Mrk 590

Abstract: We examine the long-term optical/near-infrared (NIR) flux variability of a "changing-look"active galactic nucleus (AGN) Mrk 590 between 1998 and 2007. Multiband multi-epoch optical/NIR photometry data from the SDSS Stripe 82 database and the Multicolor Active Galactic Nuclei Monitoring (MAGNUM) project reveal that Mrk 590 experienced a sudden luminosity decrease during the period from 2000 to 2001. Detection of dust reverberation lag signals between V -and K-band light curves obtained by the MAGNUM project dur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 133 publications
1
13
0
Order By: Relevance
“…Seyfert 1 galaxy PGC 50427 has a ratio of r dt /r BLR = 2.4 (Pozo Nuñez et al 2015), where r dt is a dust torus radius. The rest-frame 5100 Å AGN luminosities at the epochs of the Hβ BLR lag measurement and the dust lag measurement are L(5100 Å) ≈ 10 43 erg s −1 cm −2 for NGC 5548 with r dt /r BLR = 4.4 (Kokubo & Minezaki 2020). Mandal et al (2020) found that r dt is about a factor of 5.3 times larger than r BLR for Seyfert 1 galaxy Z229-15.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Seyfert 1 galaxy PGC 50427 has a ratio of r dt /r BLR = 2.4 (Pozo Nuñez et al 2015), where r dt is a dust torus radius. The rest-frame 5100 Å AGN luminosities at the epochs of the Hβ BLR lag measurement and the dust lag measurement are L(5100 Å) ≈ 10 43 erg s −1 cm −2 for NGC 5548 with r dt /r BLR = 4.4 (Kokubo & Minezaki 2020). Mandal et al (2020) found that r dt is about a factor of 5.3 times larger than r BLR for Seyfert 1 galaxy Z229-15.…”
Section: Discussionmentioning
confidence: 94%
“…Mandal et al (2020) found that r dt is about a factor of 5.3 times larger than r BLR for Seyfert 1 galaxy Z229-15. The dust torus innermost radii are generally larger compared to the Hβ BLR radii, by a factor of ∼ 4 for dust reverberation-mapped Seyfert galaxies (Kokubo & Minezaki 2020). NGC 3516 has r dt = 52.5 lt-days with L(5100 Å) = 10 42.63 erg s −1 cm −2 (Kokubo & Minezaki 2020), and r BLR = 7.5 lt-days with L(5100 Å) = 10 42.75 erg s −1 cm −2 obtained in our observations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The luminosity decrease of CL-AGN Seyfert 1 galaxy Mrk 590 is interpreted as an intrinsic change in the mass accretion rate of black hole (Denney et al 2014). The RM observations of Mrk 590 show r dt (faint)/r dt (bright) ∼ 0.3 between the faint and bright phases, where the dust reverberation radius decreased rapidly after the AGN ultraviolet-optical luminosity dropped (Kokubo & Minezaki 2020). However, r orb in the obscuration model should not vary with the changing accretion rate of the central black hole.…”
Section: Discussionmentioning
confidence: 98%
“…Flux variability inherent in active galactic nuclei (AGNs) and quasars is an important source of information about their physical properties and therefore has been closely investigated by astronomers for decades (see, e.g., Cristiani et al 1997;Giveon et al 1999;Vanden Berk et al 2004;Wilhite et al 2005;Magdis & Papadakis 2006;Gopal-Krishna et al 2013;Kumar et al 2015;Grier et al 2019;Yi et al 2019;Kokubo & Minezaki 2020;Luo et al 2020). The variability is observed in all spectral regions, from the X-rays to radio wavelengths, and at timescales from a few days to several years (Giveon et al 1999;Webb & Malkan 2000;Wilhite et al 2005;Schmidt et al 2012).…”
Section: Introductionmentioning
confidence: 99%